Manfaat Biodigester dalam Mengolah Limbah Perternakan menjadi Biogas sebagai Sumber Energi Baru Terbarukan di Desa Mukti Sari - M.Imam Arifandy; Norma Yulistri; Ari Armansyah; Fany Rahma Sari; Mhd. Suryalif Amsyar; Nabila Febrianti; Riski Febriansyah (Lembaga Pengembangan Kinerja Dosen, 2025)
Talking about the sustainability of life, humans cannot be separated from their dependence on energy needs. Most of the energy sources that we have used so far are fossil energy sources that are non-renewable. With the high dependence of humans on energy, innovation is needed to minimize energy limitations. One form of new renewable energy that can overcome this is Biogas. Biogas is a gas that can be obtained from the fermentation of livestock waste through technology in the form of an airtight tube called a biodigester which is useful in processing livestock waste into biogas energy. Through research that the group conducted using the literature review method, we found one village in Riau that has succeeded in utilizing biodigester technology to make biogas, namely Mukti Sari Village, Tapung District, Kampar Regency, which has now succeeded in becoming an energy independent village.